2018
DOI: 10.1111/1440-1630.12513
|View full text |Cite|
|
Sign up to set email alerts
|

Simulated versus traditional occupational therapy placements: A randomised controlled trial

Abstract: Students can achieve equivalent learning outcomes in a 40 hour simulated placement to those achieved in a 40 hour traditional placement. These findings provide assurance to students, educators and professional accreditation bodies that simulation can be embedded in occupational therapy education with good effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 23 publications
2
68
0
Order By: Relevance
“…Given that non‐inferiority of SCP versus TCP was supported by the RCT (Imms et al ., ), the economic research question and methods for bringing costs and benefits together depended on: (i) whether the SCP was found to cost less than a TCP, which would lead to cost‐minimisation analysis; and (ii) if the SCP was not less expensive than the TCP, whether there were offsetting benefits in addition to the assessed educational outcomes, that would still make the SCPs value‐for‐money. The corresponding economic methods for bringing costs and benefits together then depend on whether the benefits are monetarised and/or remain expressed in natural units of outcome (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that non‐inferiority of SCP versus TCP was supported by the RCT (Imms et al ., ), the economic research question and methods for bringing costs and benefits together depended on: (i) whether the SCP was found to cost less than a TCP, which would lead to cost‐minimisation analysis; and (ii) if the SCP was not less expensive than the TCP, whether there were offsetting benefits in addition to the assessed educational outcomes, that would still make the SCPs value‐for‐money. The corresponding economic methods for bringing costs and benefits together then depend on whether the benefits are monetarised and/or remain expressed in natural units of outcome (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…From January to November 2016, 680 students from six Australian universities undertook the unit with either the TCP or SCP component, including 570 students who consented to participate in the RCT. The educational outcomes, reported separately in a companion paper (Imms et al ., ), demonstrated the non‐inferiority of an SCP in comparison to a TCP with respect to the educational outcomes. The protocol of the RCT was published in 2017 (Imms et al ., )…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Increasing evidence has shown that practices related to SP simulation enhance student learning outcomes and clinical reasoning abilities by requiring real-time decisions 2 . However, the literature on simulations in occupational therapy and evidence supporting its use and its effectiveness in the classroom are limited to a few published articles [9][10][11][12][13][14] . Collectively, these articles report administered experiences with simulations in occupational therapy for physical disability and psychiatric patients.…”
mentioning
confidence: 99%